2019
DOI: 10.1186/s12284-019-0295-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of qBK1, a major QTL for bakanae disease resistance in rice

Abstract: Background: Bakanae disease is a fungal disease of rice (Oryza sativa L.) caused by the pathogen Gibberella fujikuroi (also known as Fusarium fujikuroi). Recently the disease incidence has increased in several Asian countries and continues to spread throughout the world. No rice varieties have been developed yet to be completely resistant to this disease. With increasing need to identify various genetic resources to impart resistance to local elite varieties, this study was carried out to identify novel quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Research groups in India (Fiyaz et al 2014 ), Korea (Kim et al 2014 ), and Taiwan (Chen et al 2019 ) used high-throughput inoculation methods to screen for resistant materials from 92, 500, and 231 diverse rice varieties, respectively. A total of 28 QTLs for bakanae resistance were mapped on rice chromosomes 1, 3, 4, 6, 8, 9, 10 and 11 (Volante et al 2017 ; Fiyaz et al 2016 ; Lee et al 2018 ; Cheon et al 2019 ; Ji et al 2018a ; Hur et al 2015 ; Lee et al 2019 ; Kang et al 2019 ; Yang et al 2006 ; Chen et al 2019 ). Chromosome 1, where 13 QTLs are located, appears to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Research groups in India (Fiyaz et al 2014 ), Korea (Kim et al 2014 ), and Taiwan (Chen et al 2019 ) used high-throughput inoculation methods to screen for resistant materials from 92, 500, and 231 diverse rice varieties, respectively. A total of 28 QTLs for bakanae resistance were mapped on rice chromosomes 1, 3, 4, 6, 8, 9, 10 and 11 (Volante et al 2017 ; Fiyaz et al 2016 ; Lee et al 2018 ; Cheon et al 2019 ; Ji et al 2018a ; Hur et al 2015 ; Lee et al 2019 ; Kang et al 2019 ; Yang et al 2006 ; Chen et al 2019 ). Chromosome 1, where 13 QTLs are located, appears to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al (2017) found that QTL qFfR1 was located in a 230 kb region of rice chromosome 1 in Korean japonica variety Nampyeong, and suggested that the three QTLs qBK1, qBK1.1, and qFfR1 might indicate the same gene. Lee et al (2019) narrowed down the position of the qBK1 locus to a 35 kb region between InDel 18 and InDel 19-14, and revealed that location of qBK1 is close to those of qBK1.1, and qFfR1, does not overlapping each other. Two additional QTLs including qB1 from Chunjiang 06 (Yang et al 2006) and qBK1 WD from Wonseadaesoo (Lee et al 2018) also were also found on chromosome 1.…”
Section: Discussionmentioning
confidence: 96%
“…The inoculation and evaluation of bakanae disease were conducted using a method that described by Lee et al (Lee et al 2019). The isolate CF283 of F. fujikuroi (imperfect stage of G. fujikuroi) were obtained from National Academy Agricultural Science in Korea.…”
Section: Evaluation Of Bakanae Resistance and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations